(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Mercury contamination of our environment in Nigeria is increasing as mining activity increases. Its exposure causes human toxicological effects which include neurotoxicity through reactive oxygen species. This study investigated the ameliorative effects of the flavonoid-rich aqueous extract of Celosia argentea (AECA) and vitamin E (VitE) in the brain of rats treated with mercuric chloride (HgCl2). Twenty-five adult male Wistar rats were randomized into five treatment groups (n=5). Group 1- control; Group 2- HgCl2 (4 mg/kg); Group 3- AECA (400 mg/kg); Group 4- HgCl2 (4 mg/kg) + AECA (400 mg/kg); Group 5- HgCl2 (4 mg/kg) + VitE (500 mg/kg). All items were administered using an oral cannula daily for 14 days. Behavioural studies were carried out on the 16th day of experiment after which rats were euthanized. Thereafter, gross, haematological and biochemical parameters [malondialdehyde (MDA), reduced glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT)] were assessed. Mercuric chloride significantly (p<0.05) reduced body weight of rats, SOD activity and GSH level but increased MDA level, CAT activity and the number of degenerated neurons in the cerebral cortex relative to control group. Microscopically, HgCl2 induced degeneration of cerebral cortical neurons and Purkinje neurons of the cerebellum. Treatment of HgCl2 and AECA and VitE caused a reversal of these HgCl2-induced alterations. The behavioural and haematological parameters were not significantly affected through the groups. The results suggest Celosia argentea Linn and vitamin E protected against mercury-induced gross, oxidative, cerebral and cerebellar damage. Both AECA and Vitamin E demonstrated neuroprotection in this experiment